An encyclopedia of world history ancient, medieval, and modern, chronologically arranged - Langer, William L. (William Leonard) 1896-1977. (Boston Houghton Mifflin, 1972)
Provides a comprehensive reference to major historical developments since the Paleolithic period.
Includes index.
Keywords: History -- Outlines, syllabi, etc; History -- Encyclopedias -- English